TATA KELOLA PROGRAM GERAKAN LITERASI SEKOLAH DI MADRASAH IBTIDAIYAH NEGERI 8 SRAGEN - Hari Kusmanto (Manajemen Pendidikan, 2022)
This study aims to describe the governance of the school literacy movement program at Madrasah Ibtidaiyah. The approach of this study is descriptive qualitative. The data used in this study is the management process of the school literacy movement. The source of data in this study is the document and the process of implementing the school literacy program. The data in this study were collected using the methods of documentation, interviews, and observations. Analysis of the research data using an interactive model. The results of this study indicate that the governance of the literacy movement program in Madrasahs is as follows (1) First, the planning of the school literacy program has been carried out by setting the objectives of the school literacy movement program. However, the planning has not been based on needs analysis (2) the organization of the school literacy program has been carried out by organizing human resources and literacy reading materials. However, the organization carried out has not included every task and responsibility of each manager (3) the implementation of the school literacy movement program has been carried out in accordance with the plan. However, evaluation has not been carried out for each activity implementation and (4) the control carried out is still limited to ensuring that the Saturday reading program is carried out or not. Control to improve the quality of the program has not been carried out. The management of the school literacy movement program needs to be managed properly, starting from the strategic planning process, organizing by providing task descriptions, implementing the program in accordance with strategic planning, and continuous evaluation.